The Impact of CSR Disclosure on Firm Value: Moderating Roles of Profitability and Firm Size - Sedani, Ni Luh Gede Ayu Sri; Ratna Sari, Maria Mediatrix (E-Jurnal Akuntansi; Vol 34 No 7 (2024)DO - 10.24843/EJA.2024.v34.i07.p12, 2024)
This study aims to gather empirical data on the impact of Corporate Social Responsibility (CSR) disclosure on firm value, using profitability and firm size as moderating variables. The research was conducted on the mining industry listed on the Indonesian Stock Exchange (BEI) for the period 2019-2022. The total sample in this study comprised 15 companies, selected using purposive sampling. The data analysis strategy employed is Moderated Regression Analysis (MRA). The results of the data analysis show that CSR disclosure positively impacts firm value. However, profitability and firm size do not moderate the impact of CSR disclosure on firm value. This study implies that it can assist investors in making informed decisions before investing. Keywords: Firm Value; CSR Disclosure; Profitability and Firm Size